La confrontation des genres au tribunal au Moyen Âge (XIVe-XVIe siècles). Une relecture des relations de couples en conflit - Martine Charageat (Genre & Histoire)
The analysis of matrimonial conflicts using the concept of gender, which goes beyond the verification of whether judges applied or not canonical law, draws more on socio-anthropological trends in the history of the married couple in the middle ages than on legal trends. The new historiographical optimism present in recent works testifies to how women were able to refuse some matrimonial situations despite the existence of domestic violence, forced sexual abstinence (impotence) and limited sentimental exchanges with their husbands. Nonetheless, this article highlights how gender determined the nature of every matrimonial conflict and its description before the judge. Gender underwrote as well the expectations litigants had in using lawsuits, given the power relationship between the sexes, even when wives and husbands sought  a judicial separation by mutual agreement.